1994
DOI: 10.1302/0301-620x.76b2.8113297
|View full text |Cite
|
Sign up to set email alerts
|

Deformity after internal fixation of fracture separation of the medial epicondyle of the humerus

Abstract: We reviewed 24 displaced fractures through the physis of the medial epicondyle of the distal humerus. One was a Salter-Harris type-II fracture-separation of the whole distal humeral epiphysis; the others involved only the medial epicondylar centre of ossification. Two cases had presented as pseudarthroses. One fracture had been treated closed in a plaster slab and 21 had had open reduction and internal fixation with sutures, Kirschner wires or Palmer nails. At 2 to 13 years later we found five types of deformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 15 publications
0
36
0
3
Order By: Relevance
“…24, 26 An avulsion of the medial epicondyle seen on the X-ray in a patient between 6 and 8 years of age, may encrypt an associated fracture of the trochlea (Salter-Haris I or III). 24,26 Although the capitellum has appeared radiologically at that age (usually since the age of Conservative treatment of posterolateral dislocation of the elbow 419 4), trochlea is not visible yet. This makes it difficult to assess the post-traumatic anatomy of the region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24, 26 An avulsion of the medial epicondyle seen on the X-ray in a patient between 6 and 8 years of age, may encrypt an associated fracture of the trochlea (Salter-Haris I or III). 24,26 Although the capitellum has appeared radiologically at that age (usually since the age of Conservative treatment of posterolateral dislocation of the elbow 419 4), trochlea is not visible yet. This makes it difficult to assess the post-traumatic anatomy of the region.…”
Section: Discussionmentioning
confidence: 99%
“…An avulsion fracture of the medial epicondyle may thus accompany a more extensive fractureseparation including the medial condyle. 18,24 This type of injury that associates posterolateral elbow dislocation with a medial condyle fracture, although extremely rare, should also be excluded. 22 The necessity of a thorough clinical examination and evaluation of the elbow before deciding the treatment approach is thus, beyond all dispute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports about injury to an unossified medial epicondyle. Skak et al 12 reported one case of this fracture that became apparent 3 months after injury and developed into a pseudoarthrosis. May et al 10 also reported an unossified medial epicondyle avulsion that was diagnosed with sonography.…”
mentioning
confidence: 99%